Environmental Factor and their Impact on the Abundance of Aquatic Plants in Iraq - Shihab, Hiba F. A.; Mohammed, Amjad Abdul Hadi; Kannah, Abdulmoneim M. A. (Journal for Research in Applied Sciences and Biotechnology, 2023)
Aquatic plants form important gatherings because they play an Important role in supporting healthy environmental systems and various human activities. As well as its geomorphological role in the formation of riverine landforms such as ridges and river Islands. The abundance and distribution of aquatic plants in different ecosystems depends on the environmental conditions, whether biotic or abiotic. In addition to the growth and diversity of different plants and also the dominance of one species in an area or the joint growth of several species, the emergence of species in a particular location is due to the different regional and local conditions of that system or location. The most influential factors in the growth and variation of plant species and their distribution in different aquatic systems are water movement, nutrients and the bottom of that system. Also, other physical factors such as light, temperature, and chemical factors such as salinity, dissolved gases, and pH which have independent or overlapping effects on the distribution, diversity, and production of plants.